Comparison of short- and medium-term clinical outcomes of ST elevation myocardial infarction patients with spontaneous reperfusion: Early vs. late dual antiplatelet: Comparación de los resultados clínicos a corto y mediano plazo en pacientes con infarto agudo de miocardio con elevación del ST y reperfusión espontánea: Iniciación temprana versus tardía de la terapia antiplaquetaria dual - Bakhtiar, Nurbaeti; Hakim Alkatiri, Abdul; Muzakkir, Akhtar Fajar; Djafar, Zaenab; Zainuddin, Andi Alfian; Qanitha, Andriany (Gaceta Médica de Caracas, 2025)
Background: Cardiovascular disease remains the leading cause of mortality worldwide, and its global burden continues to rise. Previous studies have shown that the incidence of spontaneous reperfusion in STEMI patients can reach up to 30 %, and the timing of antiplatelet administration is associated with increased stable spontaneous perfusion and better prognosis and clinical outcomes. Objective: This study aims to compare the short- and medium-term clinical outcomes of STEMI patients who underwent spontaneous reperfusion and received early versus late dual antiplatelet treatment at the Integrated Heart Center of Dr. Wahidin Sudirohusodo Hospital, Makassar.